2009
DOI: 10.1182/blood-2008-09-178046
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lymphoproliferative disorders after allogeneic hematopoietic cell transplantation

Abstract: We evaluated 26 901 patients who underwent allogeneic hematopoietic cell transplantation (HCT) at 271 centers worldwide to define patterns of posttransplantation lymphoproliferative disorders (PTLDs). PTLDs developed in 127 recipients, with 105 (83%) cases occurring within 1 year after transplantation. In multivariate analyses, we confirmed that PTLD risks were strongly associated (P < .001) with T-cell depletion of the donor marrow, antithymocyte globulin (ATG) use, and unrelated or HLA-mismatched grafts (URD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
329
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(356 citation statements)
references
References 30 publications
22
329
3
2
Order By: Relevance
“…For immunosuppressed patients, it appears clear that T-cell deficiency favors appearance of latency III malignancies (3), that adoptive T-cell therapy can prevent this (4,5), and that T-cell therapy fails if the EBV strain in question does not express crucial CD8 + T-cell epitopes in a latency III protein (50). Regarding infection in immunocompetent carriers, there were early arguments against a T-cell surveillance of latency III (51), but later studies showed that latency III-associated CD8 + T-cell epitopes are in fact under a selective pressure that depends on the frequency of HLA class I allotypes in a population (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…For immunosuppressed patients, it appears clear that T-cell deficiency favors appearance of latency III malignancies (3), that adoptive T-cell therapy can prevent this (4,5), and that T-cell therapy fails if the EBV strain in question does not express crucial CD8 + T-cell epitopes in a latency III protein (50). Regarding infection in immunocompetent carriers, there were early arguments against a T-cell surveillance of latency III (51), but later studies showed that latency III-associated CD8 + T-cell epitopes are in fact under a selective pressure that depends on the frequency of HLA class I allotypes in a population (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…In an international study of 26,901 allogeneic HCT recipients during 1964–1994, the observed to expected ratio of PTLD was 29.7. 13,80 MDS/AML risk after allogeneic HCT is thought to be comparable to that of other cancer survivors who have received particular cytotoxic chemotherapeutic agents and radiotherapy, with such risks often exceeding 10-fold. 81 There is also some evidence that MDS/AML risks may be even higher after autologous HCT because of the substantial cumulative doses received during pre-transplant chemotherapy and radiotherapy, chemotherapy-based stem cell mobilization and HCT conditioning.…”
Section: Magnitude Of Riskmentioning
confidence: 99%
“…For example, immune activation or chronic immune damage of tissues from GVHD could act synergistically with viruses to impact risk of cancers such as oral cavity SCC. 80,172175 Similarly, immunosuppression could lead to the reappearance of latent HPV infection, affecting risk of cutaneous SCC or cervical cancer. 176,177 …”
Section: Non-transplant-related Risk Factorsmentioning
confidence: 99%
“…2,3 Published experience regarding the incidence of EBV-PTLD after allogeneic HCT ranges between 0.5 and 17% and is mainly based on single-centre experiences or retrospective studies limited by small numbers and diverse patient characteristics. [4][5][6][7] However, Landgren et al 8 collected data on 127 EBV-PTLD cases from 271 centres and found an elevated risk for developing PTLD especially in the first year after HCT (83%) with the highest occurrence during the first 6 months. However, late EBV-PTLD could be observed even up to 10 years after HCT.…”
Section: Introductionmentioning
confidence: 99%